ANALISIS PENGARUH KESEMPATAN KERJA, BELANJA DAERAH DAN INVESTASI TERHADAP PERTUMBUHAN EKONOMI SUMATERA BARAT - Fitri, Erlina; , Ansofino, , Ansofino; Afriza, Rina (Pendidikan Ekonomi, 2014)
ABSTRACT Issues that are examined in this study is an analysis of the effect of employment opportunities, region expenditure and investment on the economic growth of West Sumatra between 2000 and 2011. Methodology used in this study is the method of OLS (Ordinary Least Square). The data used are time series data in the form data annual employment opportunities, region expenditure and investment of West Sumatra. Collected through the documentation on the relevant agencies. The results showed that, first : Employment Opportunities positive and significant impact on economic growth indicated by the coefficient value of 1,047 to 3,484 tcount > ttable of 1.860 and a probability of 0.008 < α = 0.05 level. Second : region expenditure is positive and significant impact on economic growth is indicated by a coefficient of 0.050 with 2.107 tcount > ttable probability of 1.860 and 0.068. Third : Investment positive and significant impact on economic growth indicated by a coefficient of 0.266 with a value of 4,175 tcount > ttable at 1.860 and probability of 0.0031. Fourth : Employment Opportunities, Region Expenditure and Investment jointly positive and significant impact on economic growth indicated by the value of F at 328.6095 while the Ftable at level α = 5% error obtained is 3.84 with a value of R-square of 0.9930, which means at 99.30% economic growth is influenced by variables employment opportunities, and investment region expenditure while the rest clarified by other variables. From this research, the variables that most influence the economic growth of West Sumatra is a job opportunity with a coefficient value of 1,047 and 3,484 tcount > ttable of 1.860 and a probability of 0.008 < α = 0.05 level. So for further research is recommended to include other variables that affect economic growth in West Sumatra.